2014
DOI: 10.1017/jwe.2014.15
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of the California Winegrape Supply Chain

Abstract: This study investigates factors influencing coordination of the California grape and wine supply chain. Results corroborate prior findings that quality considerations and needs to protect investments in specialized or durable assets significantly increase usage of more formal coordination mechanisms, such as formal contracts and vertical integration or ownership. Consistent with findings for other industries, such investments are associated with greater contract complexity and inclusion of enforcement provisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…Both studies found that wineries had more in luence on production practices under contracts for higher-quality grapes; contracts for lower-quality grapes relied more on quality metrics and inancial incentives. Building on this research, Franken (2014) found that perceived dif iculty or uncertainty associated with measuring grape quality decreased the probability of informal verbal agreements and increased reliance on formal written contracts for winegrapes in California. According to the organizational economics literature (Mahoney 1992), when measuring quality is dif icult, uncertain, or costly, contract provisions can stipulate best practices that have proven effective in delivering a desired level of quality if their use is easily veri ied (i.e., the task is programmable).…”
Section: Grape Procurementmentioning
confidence: 91%
See 2 more Smart Citations
“…Both studies found that wineries had more in luence on production practices under contracts for higher-quality grapes; contracts for lower-quality grapes relied more on quality metrics and inancial incentives. Building on this research, Franken (2014) found that perceived dif iculty or uncertainty associated with measuring grape quality decreased the probability of informal verbal agreements and increased reliance on formal written contracts for winegrapes in California. According to the organizational economics literature (Mahoney 1992), when measuring quality is dif icult, uncertain, or costly, contract provisions can stipulate best practices that have proven effective in delivering a desired level of quality if their use is easily veri ied (i.e., the task is programmable).…”
Section: Grape Procurementmentioning
confidence: 91%
“…The responses ranged from 3 to 5 with an average of 4.30, indicating that Illinois winery operators view grape quality as fairly easy to measure (Table 1). Relevant quality attributes, on the other hand, were perceived as more dif icult to measure by participants in Franken's (2014) study of the winegrape supply chain in California; for a comparable question, the responses ranged from 2 to 5 with an average value of 3.70. The difference may re lect greater attention to quality attributes that are objectively measured (e.g., sugar content in brix and acidity in pH) and less attention paid to attributes that are subjectively measured (i.e., color and lavor) in emerging wine regions.…”
Section: Measures Of Conceptual Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the WSC, through links previously built between the members, it is possible to identify different types of flows. Of particular importance are the physical flows (raw materials, semifinished products, and finished products) and the information flows that enable monitoring of physical flows (Lam et al, 2013;Franken, 2014;Song et al, 2016). Craighead et al (2007) identify these three types of flows more precisely: (1) "forward" flow corresponds to the movement of materials and products from a WSC member located upstream to a WSC located downstream; (2) "backward" flow refers to the flow of materials from a WSC member located down stream to a WSC member located upstream (e.g.…”
Section: Flowsmentioning
confidence: 99%
“…Sectors such as the automotive industry, but also the personal computer, convenience goods and retailing industries have attracted attention with regard to the performance of their supply chains. However, in the case of the wine industry, despite Franken's (2014) focus on the use of formal coordination mechanisms in the California wine grape supply chain, qual ity considerations have been paramount to protect investment in special assets. The reasons for the lack of interest in the wine supply chain (WSC) are: (1) the traditional character of the industrial and logistical processes; and (2) a product aimed at a gourmet clientele which, primarily, is searching for thrills in terms of taste.…”
Section: Introductionmentioning
confidence: 99%